Pengaruh Kompetensi dan Budaya Organisasi Terhadap Kepuasan Kerja dan Dampaknya Pada Kinerja Karyawan Bank Sumsel Babel di Palembang - Nurul Mardiyyah Pratiwi (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2019)
This study aims to determine the effect of competence and organizational culture on job satisfaction and its impact on employees’ performance in the Bank Sumsel Babel. The design of this study is associative research by connecting between independent and bound variabels. The data used in this study are primery and secondary data, and the sample of this study is 250 employees of Bank Sumsel Babel. The Analysis method used is Path Analysis and though testing validity and reliability. Test the data used to determine the characteristics of the data, namely the normality test and linearity tes. The model test used cosisted of a multicolinearity test and a heterodiversity test, aided by an SPSS for windows analysis tool with a significant level of 0,05. The result of Path analysis showed competence, organizational culture and job satifaction joinly had a significant effect on employees’ performance. Competence, organizational culture and job satifaction partially have a significant effect on employees’ performance.